Conceptualizing Conflict-Related Child and Early Marriage as Insecurity: At the Intersection of Gender and Age. Issue 4 (26th October 2022) - Lee-Koo, Katrina; Gordon, Eleanor
Abstract: Child, early, and forced marriage (CEFM) remains prevalent worldwide. Rates are especially high in areas affected by crisis and conflict. CEFM predominately impacts girls, who are married to adult men; it increases their vulnerability to other threats, including physical, economic, and health insecurities, and curtails access to education. Moreover, because of these resultant threats, CEFM entrenches gender inequality and compromises the extent to which girls engage in community-based crisis response and recovery, thereby undermining efforts to build inclusive, meaningful, and sustainable peace and security. In spite of this, there is little consideration of CEFM in security theorizing or practice. This article explores the security-related causes and effects of CEFM on adolescent girls in conflict-affected contexts by drawing from research conducted in four crisis contexts: Lake Chad (Niger, Nigeria, and Cameroon), South Sudan and Uganda, Lebanon (Beirut), and Bangladesh (Cox's Bazar). The article argues that, using an age-responsive critical feminist security framework, clear links can be made between gender inequality, CEFM in adolescent girls, and security.